2009
DOI: 10.1097/fbp.0b013e3283242f57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a metabotropic glutamate receptor group II agonist LY354740 in animal models of positive schizophrenia symptoms and cognition

Abstract: It has been proposed that activation of metabotropic glutamate receptor subtype 2/3 (mGluR2/3) may induce both antipsychotic and anxiolytic effects. The aim of this study was to evaluate further the effect of the mGluR2/3 agonist, LY354740 [(+)-2-aminobicyclo(3.1.0)hexane-2,6-dicarboxylate monohydrate] in animal models relevant to both psychotic and cognitive impairment in schizophrenia. The elevated plus maze was used to select the doses for further experiments, LY354740 induced anxiolytic-like effects at dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 46 publications
6
53
0
Order By: Relevance
“…The therapeutic potential has however been shown to vary between different mGluR2/3 agonists, as some agonists failed to improve PCP-induced behavioral impairments (Schlumberger et al, 2009). Treatment specifically with the mGluR2/3 agonist LY379268 used in this study has been shown to reduce MK-801-induced hippocampal-PFC synaptic transmission and gamma band oscillation; this supports the utility of LY379268 to restore the balance between glutamatergic and GABAergic neurotransmission in cortical and subcortical regions (Blot et al, 2013;Hiyoshi et al, 2014).…”
Section: The Mglur2/3 Agonist Ly379268 Restores Nmda-r and Gabaa-r Exsupporting
confidence: 63%
“…The therapeutic potential has however been shown to vary between different mGluR2/3 agonists, as some agonists failed to improve PCP-induced behavioral impairments (Schlumberger et al, 2009). Treatment specifically with the mGluR2/3 agonist LY379268 used in this study has been shown to reduce MK-801-induced hippocampal-PFC synaptic transmission and gamma band oscillation; this supports the utility of LY379268 to restore the balance between glutamatergic and GABAergic neurotransmission in cortical and subcortical regions (Blot et al, 2013;Hiyoshi et al, 2014).…”
Section: The Mglur2/3 Agonist Ly379268 Restores Nmda-r and Gabaa-r Exsupporting
confidence: 63%
“…mGlu2/3-receptor agonists have been reported not to improve either the NMDA-receptor antagonists-induced impairment of working memory (39) or the NMDAreceptor antagonist-induced impairment of object recognition (40), although mGlu2/3-receptor agonists improved object recognition impairment in rodents reared in social isolation or in mice lacking the pituitary adenylate cyclase-activating polypeptide (41 -43). Moreover, the stimulation of the mGlu2 receptor or the blockade of the mGlu1 receptor reportedly caused cognitive impairment itself (19,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are negative results as well. More specifically, mGlu2/3 receptor agonists were shown not to be able to antagonize cognition-impairing effects of PCP in other studies in which experimental protocols may have been optimized to detect cognition-impairing effects of mGlu2/3 agents (Schlumberger et al, 2009). Furthermore, failures to reverse certain cognitive effects of PCP may be related to the fact that PCP-like agents are able to impair performance in behavioral tasks via a number of different mechanisms, including motor activation, behavioral disinhibition, and induction of state-dependence.…”
Section: Mglu2/3 Receptor Agonistsmentioning
confidence: 99%